ANALYZING THE EFFECT OF VIRTUAL ATMOSPHERIC CUES, SALES PROMOTIONS, AND SITUATIONAL FACTORS ON ONLINE IMPULSE BUYING IN MANADO - Longdong, Esther Yosilia Ernawati; Pangemanan, Sifrid S. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
The growth of e-commerce in Indonesia has increased significantly in recent years, while Indonesia’s shoppers tend to be more impulsive, and it includes shoppers in Manado. There are many factors that could possibly affect online impulse buying. Some of them are virtual atmospheric cues, sales promotions, and situational factors. The aim of this study is to analyze the effect of virtual atmospheric cues, sales promotions, and situational factors on online impulse buying. This research collects primary data through questionnaires and uses Multiple Regression. Population observed is internet users in Manado who have ever bought products online with 60 respondents as the sample size. The result of this study shows that sales promotions and situational factors have significant positive effect on online impulse buying, while virtual atmospheric cues does not have that effect. To attract more consumers to buy impulsively, the recommendations for online shop owners are to keep offering sales promotions effectively, giving affordable price to increase purchasing power of consumer, and also maintaining the 24 hours services and easiness of accessing online shop to stimulate consumer to spend more time at the online shop. Keywords: impulse buying, virtual atmospheric cues, sales promotions, situational factors